The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1089/ped.2011.0081
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Environmental Control and Asthma Outcomes Among Urban Latino, African American, and Non–Latino White Families

Abstract: Latino and African American children with asthma are at increased risk for asthma morbidity compared with non-Latino White children. Environmental control (ie, environmental exposures and family strategies to control them) may contribute to greater asthma morbidity for ethnic minority children living in urban environments. This study examined ethnic differences in a semi-structured assessment of environmental control, associations between environmental control and asthma outcomes (asthma control, functional li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The FAMSS has been used in cross sectional and treatment outcome studies and has been validated with minority samples 60 and in English and Spanish. 61 Internal consistency has been very good in prior studies (Cronbach’s α = .84) 62 and in the current sample (Cronbach’s α = .76).…”
Section: Participant and Methodssupporting
confidence: 51%
“…The FAMSS has been used in cross sectional and treatment outcome studies and has been validated with minority samples 60 and in English and Spanish. 61 Internal consistency has been very good in prior studies (Cronbach’s α = .84) 62 and in the current sample (Cronbach’s α = .76).…”
Section: Participant and Methodssupporting
confidence: 51%
“…Some studies suggest a genetic link between the incidence and prevalence of asthma and African American race (Smith et al, 2008; Flores et al, 2012), while others reported that life style and home environment may be the source of ethnic disparities (Sun and Sundell, 2011). Another explanation for the high prevalence of asthma among African Americans is that they are more likely to live in older urban homes in the U.S. (Aligne et al, 2000; Everhart et al, 2011). Families with lower income may have higher concentrations of indoor contaminants because poverty causes them to live in more deteriorating structures as those with higher income.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to asthma medication at study entry was also queried using a 5-point Likert scale: 1 = never to almost never missed, 2 = occasionally missed, 3 = missed about half the time, 4 = missed more than half the time, to 5 = missed almost all the time. 18,19 Caregiver perception of allergy status Before allergy skin prick testing, caregivers were asked questions about their child's nasal symptoms: (1) Do you think your child has allergies, and (2) has your doctor ever told you or diagnosed your child with allergies? Caregivers were asked whether their child ever had allergy testing before the research clinic visit.…”
Section: 15mentioning
confidence: 99%